If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 16 + -1(-13) + -1(-5) = x Multiply -1 * -13 16 + 13 + -1(-5) = x Multiply -1 * -5 16 + 13 + 5 = x Combine like terms: 16 + 13 = 29 29 + 5 = x Combine like terms: 29 + 5 = 34 34 = x Solving 34 = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 34 + -1x = x + -1x Combine like terms: x + -1x = 0 34 + -1x = 0 Add '-34' to each side of the equation. 34 + -34 + -1x = 0 + -34 Combine like terms: 34 + -34 = 0 0 + -1x = 0 + -34 -1x = 0 + -34 Combine like terms: 0 + -34 = -34 -1x = -34 Divide each side by '-1'. x = 34 Simplifying x = 34
| 6(y-4)=5[17-3(2y-13)] | | 4-5+7k=33 | | -9-200x+(0.015)(100)= | | (-16)-6+(-5)=x | | 12+0.4(x-2)=10 | | 6(x+2)+4=-6 | | 52x=104 | | 8y-5=6y+7 | | -33m-14=85 | | 5x+5x+3+8=5x+4+4x | | -r+259=-124 | | -2x^2+12x+3=0 | | 3(3+2r)=5-6(r+2) | | 3(2x-4)=5(x+6) | | 7x-6-4x=4x-3 | | 2.1x+1=7 | | 9x-3x=-26+2 | | 7-7x=29x+21 | | 17X^43=100000 | | 145-13= | | 6x+4-4=20 | | 2(w+6)+4=2w+16 | | 75+13w=335 | | 9m=3(8m+30) | | 10+2x-x^2=0 | | 9x+9=11x-3 | | 81-6x=7x | | 9x(x+1)=10 | | 1-2x=3x-9 | | -4x-12=2x+12 | | 3(2x+2)=3x+24 | | x-12x+33=0 |